Guidelines For Teaching Management To Increase The School Effectiveness Under Roi-Et Secondary Education Service Area Office - Norateethan, Puangpet; Suwanseantavee, Vimonporn (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this thesis research are: 1) to study the current situation, desired situation, and necessary requirements for teaching management in order to increase the effectiveness of educational institutions under the supervision of the Secondary Educational Service Area Office in Roi Et province and 2) to study the strategies and guidelines for teaching management in order to increase the effectiveness of educational institutions under the supervision of the Secondary Educational Service Area Office in Roi Et province. It is a mixed methods research (Mix Method). The sample group in this research are 335 school administrators and teachers from secondary schools under the supervision of the Secondary Educational Service Area Office in Roi Et province. The research tool to collect data is a questionnaire with a reliability value of 0.93 and a validity value ranging from 0.67-1.00. The results showed that 1. The current state of teaching management to enhance the effectiveness of education is at a moderate level. The desired state of teaching management to maximize the effectiveness of education is at the highest level, and the overall level of necessity is valued at 0.35. The areas of objective setting for teaching management are the highest, followed by teaching management, content setting for teaching management, and the use of teaching management media. The lowest area is the measurement and evaluation of teaching management outcomes. 2. Guidelines for teaching and learning management to increase the effectiveness of schools under the Roi Et Secondary Educational Service Area Office consist of teaching and learning management in accordance with the basic education core curriculum, setting objectives in line with learning standards, adjusting the difficulty of content according to the potential of learners, using up-to-date and diverse innovative media suitable for learners, and diverse measurement and evaluation methods that consider individual differences.